Cooperation between the Horn of Africa and the European Union - - Dorothy Chebet Rotich (Vestnik RUDN. International Relations, 2011)
This article outlines the causes of conflict in the Horn of Africa and the joint EU-Africa strategies undertaken by the European Union and the Horn of Africa partners to bring sustainable peace to the region.